THE EFFECT OF ENTERPRISE RISK MANAGEMENT AND FIRM FINANCIAL PERFORMANCE: EMPIRICAL STUDY ON MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Abraham Jordy Winarto; Anis Chariri (Diponegoro Journal of Accounting, 2022)
The purpose of this study is to analyze the effect of enterprise risk management on firm financial performance. Those factors include risk committee, risk map, COSO and ISO framework.This study is done quantitatively. Secondary data is collected through annual report, Bloomberg Finance Laboratories and IDX website using purposive sampling. The population of this research is manufacturing companies as listed on IDX around 2018-2018 with the total of samples are 74 companies. The obtained data then were examined by using multiple linear regression with SPSS 25 software.The results of the study indicate the findings show that ISO framework positively affect the firm financial performance while risk committee, risk map and COSO framework does not significantly affect the firm financial performance.